2020
DOI: 10.3390/coatings10090816
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Some Flexographic Printing Process Conditions on the Optical Density and Tonal Value Increase of Overprinted Plastic Films

Abstract: The print quality of prints performed with flexographic printing technology is influenced by various parameters such as viscosity of the printing inks, printing substrates, plates, anilox rolls, etc. The aim of this work is to analyze the influence of ink viscosity, printing plate and printing base on selected properties of print quality, such as optical density of full tone area and the increase of tonal value (TVI). Additionally, the printed dots on 5, 15, 30, 50 and 75% of half tone area were investigated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…[ 32 ] Havlinova et al [ 33 ] has suggested the flow time in the range 18–35 s to achieve proper inking of the anilox roller in the printing units. In our previous work, [ 34 ] we observed that printing with maximum ink viscosity in industrial conditions causes some difficulties. Hence, we have chosen 31 s as a maximum flow time.…”
Section: Resultsmentioning
confidence: 99%
“…[ 32 ] Havlinova et al [ 33 ] has suggested the flow time in the range 18–35 s to achieve proper inking of the anilox roller in the printing units. In our previous work, [ 34 ] we observed that printing with maximum ink viscosity in industrial conditions causes some difficulties. Hence, we have chosen 31 s as a maximum flow time.…”
Section: Resultsmentioning
confidence: 99%
“…Another way to solve this problem requires much more commitment, and it also costs more. The quality of the print is greatly determined by the preparatory work in the prepress and printing processes [35]. Image processing in prepress should be made again by using a "bump-up" curve that sets 2% as the minimum value, thus ensuring the correct ratio between the anilox line screen and the plate line ruling.…”
Section: Dot Deformation Caused By Incorrect Settingsmentioning
confidence: 99%
“…Further complications arise due to the desiccation of ink remnants within the cells, which has implications for the ceramic surface of the roll. During printing, the ink tends to dry on the base and peripheries of the anilox cells, progressively diminishing the ink capacity [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%